The Quality of Frozen Buffalo Sperm Following Sexing using Bovine Serum Albumin (BSA) Column and Swim-Up (SU) Methods - Masrizal, Masrizal; Afriani, Tinda; Wahyudi, Dwiki; Saharani, Savira; Ananda, Ananda (Buletin Peternakan, 2024)
This study assesses the impact of two sperm sexing techniques, the Bovine Serum Albumin (BSA) column method, and the swim-up (SU) method, on frozen buffalo spermatozoa quality.  A total of 50 straws of frozen buffalo semen were used in this study. Spermatozoa quality was evaluated before (post thawing) and after the spermatozoa sexing process. Spermatozoa trapped in BSA upper fraction, BSA lower fraction, SU upper fraction, and SU lower fraction were separately evaluated. The parameters measured consisted of  spermatozoa motility, viability, intact plasma membrane, intact acrosome cap, and spermatozoa DNA integrity. The results indicated that the quality of post-thawing buffalo spermatozoa remained relatively high, with motility at 41%, viability at 64.48%, intact plasma membrane at 55.42%, intact acrosome cap at 47.12%, and sperm DNA integrity at 74.94%. However, the use of the BSA column method significantly (p<0.05) decreased spermatozoa quality in both the upper and lower fractions, resulting in motility levels of 34% and 32%, viability rates of 49.36% and 44.71%, intact plasma membrane percentages of 44.78% and 37.13%, intact acrosome cap figures of 37.58% and 33.27%, and sperm DNA integrity levels of 74.76% and 72.45%, respectively. In contrast, the application of the SU method proved effective in preserving post-thawing spermatozoa quality, yielding motility rates of 42% and 41%, viability levels of 63.62% and 62.78%, intact plasma membrane percentages of 54.42% and 54.74%, intact acrosome cap figures of 46.94% and 45.74%, and sperm DNA integrity values of 70.57% and 70.01%, respectively. In summary, after freezing, the SU method excel the BSA column method in maintaining the quality of buffalo spermatozoa post-thawing.